Polemik presiden wanita dalam tinjauan Islam - Jaiz, Hartono Ahmad. (Pustaka Al-Kautsar, 1998)
Women presidents according to Islamic viewpoints.
Includes bibliographical references (p. 122-125).
Women presidents according to Islamic viewpoints.
Includes passages in Arabic.
Keywords: Legal status. / homoit / https://homosaurus.org/v3/homoit0000712; Islam and politics / Indonesia. / http://id.loc.gov/authorities/subjects/sh85068422; Women / Political activity / Indonesia / Islam.; Women presidents / Indonesia / Religious aspects / Islam.; Muslim women / Legal status, laws, etc. / Indonesia.; Women (Islamic law) / Indonesia.